A coding polymorphism in matrix metalloproteinase 9 reduces risk of scarring sequelae of ocular Chlamydia trachomatis infection - Joof Hassan M; Burton Matthew J; Holland Martin J; Cooke Graham; Natividad Angels; Rockett Kirk; Kwiatkowski Dominic P; Mabey David CW; Bailey Robin L (BMC, 2006)
Abstract Background Trachoma, an infectious disease of the conjunctiva caused by Chlamydia trachomatis, is an important global cause of blindness. A dysregulated extracellular matrix (ECM) proteolysis during the processes of tissue repair following infection and inflammation are thought to play a key role in the development of fibrotic sequelae of infection, which ultimately leads to blindness. Expression and activity of matrix metalloproteinase 9 (MMP-9), a major effector of ECM turnover, is up-regulated in the inflamed conjunctiva of trachoma subjects. Genetic variation within the MMP9 gene affects in vitro MMP9 expression levels, enzymatic activity and susceptibility to various inflammatory and fibrotic conditions. Methods We genotyped 651 case-control pairs from trachoma endemic villages in The Gambia for coding single nucleotide polymorphisms (SNPs) in the MMP9 gene using the high-throughput Sequenom® system. Single marker and haplotype conditional logistic regression (CLR) analysis for disease association was performed. Results The Q279R mutation located in exon 6 of MMP9 was found to be associated with lower risk for severe disease sequelae of ocular Chlamydia trachomatis infection. This mutation, which leads to a nonsynonymous amino-acid change within the active site of the enzyme may reduce MMP-9-induced degradation of the structural components of the ECM during inflammatory episodes in trachoma and its associated fibrosis. Conclusion This work supports the hypothesis that MMP-9 has a role in the pathogenesis of blinding trachoma.